6β-HYDROXYTESTOSTERONE, A CYTOCHROME P450 1B1-TESTOSTERONE-METABOLITE, MEDIATES ANGIOTENSIN II-INDUCED RENAL DYSFUNCTION IN MALE MICE - Pingili, Ajeeth K. (Hypertension, 2016)
6β-hydroxytestosterone, a cytochrome P450 1B1-derived metabolite of testosterone, contributes to the development of angiotensin II-induced hypertension and associated cardiovascular pathophysiology. In view of the critical role of angiotensin II in the maintenance of renal homeostasis, development of hypertension and end organ damage, this study was conducted to determine the contribution of 6β-hydroxytestosterone to angiotensin II actions on water consumption and renal function in male Cyp1b1(+/+) and Cyp1b1(−/−) mice. Castration of Cyp1b1(+/+) mice or Cyp1b1(−/−) gene disruption minimized the angiotensin II-induced increase in water consumption, urine output, proteinuria, and sodium excretion and decreases in urine osmolality. 6β-hydroxytestosterone did not alter angiotensin II-induced increases in water intake, urine output, proteinuria, and sodium excretion or decreases in osmolality in Cyp1b1(+/+) mice, but restored these effects of angiotensin II in Cyp1b1(−/−) or castrated mice Cyp1b1(+/+) mice. Cyp1b1 gene disruption or castration prevented angiotensin II-induced renal fibrosis, oxidative stress, inflammation, urinary excretion of angiotensinogen, expression of angiotensin II type 1 receptor, and angiotensin converting enzyme. 6β-hydroxytestosterone did not alter angiotensin II-induced renal fibrosis, inflammation, oxidative stress, urinary excretion angiotensinogen, expression of angiotensin II type 1 receptor, or angiotensin converting enzyme in Cyp1b1(+/+) mice; however, in Cyp1b1(−/−) or castrated mice Cyp1b1(+/+) mice, it restored these effects of angiotensin II. These data indicate that 6β-hydroxytestosterone contributes to increased thirst, impairment of renal function, and end organ injury associated with angiotensin II-induced hypertension in male mice and that cytochrome P450 1B1 could serve as a novel target for treating renal disease and hypertension in males.